Implementasi Maximum Power Point Tracking pada Photovoltaic Berbasis P&O-Fuzzy - Machmud Effendy; Nur Alif Mardiyah; Khusnul Hidayat (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
Maximum Power Point Tracking (MPPT) technology is an alternative solution to improve efficiency of solar cells (photovoltaic). The main part of MPPT technology is DC-DC converter circuit and control algorithm. This paper proposes a control algorithm Perturbation and Observe (P&O)-Fuzzy on MPPT, which can improve the efficiency of solar cells, and simultaneously comparing the control algorithms P&O and P&O-Fuzzy. Synchronous buck converter is used to reduce the voltage of solar cells. The buck converter is controlled using P&O and P&O-Fuzzy algorithms. These algorithms use two inputs; change of power and change of voltage, produced by the solar cell. MPPT technology has been tested using solar cells with a capacity of 50 Watt as a source of electrical energy, battery 12V/45aH as energy storage, and resistor as load. The test results indicate that the P&O algorithm has an efficiency of 86% with rise time (tr) and steady state time (ts) at 0.45 seconds, while the P&O-Fuzzy algorithm has an efficiency of 89% with rise time (tr) and steady state time (ts) at 0.3 seconds.